Educação Física e a Cultura da Prática - do Carmo Junior, Wilson [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2011)
physical education with a discipline or field has reached the status and scope in all spheres of contemporary culture. Not by chance that issues relating to body and human movement in recent years have been the focus of studies, especially understanding of the need to reflect on new concepts in physical education. Science in the traditional sense, as a method of analysis supports the idea of scientific rigor, but is fundamental reflection. This essay seeks the interface between science and philosophy, on which discussions can take other visibilities in physical education as an activity of the culture. With interdisciplinary approaches and thinking about body movement, focus on scientific concepts and philosophical traverse historically a possible way to rethink the design physical education.

A educação física com uma disciplina ou área do conhecimento tem alcançado status e abrangência em todas as esferas da cultura contemporânea. Não por acaso que as questões relativas ao corpo e ao movimento humano, nos últimos anos foram foco de estudos, sobretudo compreensão da necessidade de refletir sobre novos conceitos dentro da educação física. A ciência, no sentido tradicional, enquanto método de análise sustenta a idéia do rigor científico, porém é condição fundamental a reflexão. Este ensaio procura a interface entre ciência e filosofia, cujo debate poderá dar outras visibilidades na educação física como atividade da cultura. Com abordagens interdisciplinares e a reflexão sobre o corpo o movimento, como foco nos conceitos científicos e filosóficos percorrerá historicamente um caminho possível para repensar o projeto educação física.
Physical Education and the Culture of Practice
Keywords: Physical education; Philosophy and culture; Science and human movement